Optimalisasi Ruang Gerak Siswa pada Area Komunal Sekolah Dasar (Jurnal TekstuReka, 2023)
In addition to teaching and learning activities, in elementary schools there are interactions between students and teachers, as well as students and students. This study focuses on activities in the communal area of a primary school to be analyzed according to the needs of users. It is hoped that the results of this research can provide solutions for related parties in the development of communal areas in accordance with their existing activities and conditions. Research is descriptive quality research with data collection through questionnaires, surveys and interviews from teachers/ school administrators. Sampling interviews to determine aspects of the needs of space users, literature studies to find out the standards and aspects needed to determine the factors that influence the design of communal areas, and the characteristics of users, the students. Based on the results of the analysis, it can be concluded that space optimization can be done by means of communal areas made with open-layout in order to facilitate student movement and can be used tentatively at certain times, it is also necessary to manage access times and types of student activities when there is a change of class or communal area activities, considering the limited space. Research can be continued by comparing with similar case studies to find rhythms and solutions that can be applied in general or specifically per object of study.